Accumulation of radio-iron and plutonium, alone and in combination, in Pseudomonas putida grown in liquid cultures. (24th November 2021) - Manglass, Lisa M; Wintenberg, Molly; Vogel, Charlotte; Blenner, Mark; Martinez, Nicole E
Abstract: The impact of low doses of ionising radiation on biological and environmental systems have been historically difficult to study. Modern biological tools have provided new methods for studying these mechanisms but applying these tools to a dose–response relationship may require refinement of dosimetric techniques that incorporate a detailed understand of radionuclide accumulation in biological cells, particularly when assessing the impact of low doses of ionising radiation. In this work Pseudomonas putida ( KT2440) grown in liquid culture was exposed to low dose rates (10–20 mGy d −1 ) of 239 Pu and 55 Fe, both alone and in combination, for a period of 20 days, and the accumulation of 239 Pu and 55 Fe in cell pellets was analysed via liquid scintillation counting. The study also considered of cells grown with 239 Pu and stable Fe (primarily 56 Fe). In addition to the analysis of cell pellet and media samples, this work includes analysis of the radiological content of ribonucleic acid extraction samples to examine uptake of radionuclides. Results indicate that 239 Pu inhibited the uptake of 55 Fe, and that the presence of stable and radioactive isotopes of Fe in cultures may promote pathways for Fe accumulation that are used by 239 Pu. The work herein provides foundational insight into future dosimetric models for our work with environmental bacteria.